2015
DOI: 10.15578/squalen.v10i3.175
|View full text |Cite
|
Sign up to set email alerts
|

Non-Target Screening Method for the Identification of Persistent and Emerging Organic Contaminants in Seafood and Sediment from Jakarta Bay

Abstract: Identification of persistent and emerging organic contaminants in green mussels (Perna viridis), various fishes, banana shrimp (Penaeus merguiensis) and sediment samples from Jakarta Bay has been employed. A non-target GC-MS screening approach has identified more than 60 individual organic compounds from the whole fractions either non-polar, semi-polar or acidic-polar compounds. The substances comprised as persistent organic pollutants (POPs) including DDT (dichlorodiphenyl trichloroethane) and its metabolites… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Similar to DIPNs contaminant, concentration of PMN in green mussel was relatively higher than that in fish, crab, and shrimp. Even though m-terphenyl was not detected in seafood from Jakarta Bay, this compound is present in water and sediment samples as reported by Dwiyitno et al (2015) that indicates contamination occurrence at lower concentration and/or less persistence than DIPNs and PMN. This could be seen from the lower octanol/water coefficient (log K ow ) of mterphenyl (5.52) compared to that of DIPNs (6.08).…”
Section: Contamination Of Dipns In Seafood Samples Frommentioning
confidence: 52%
See 1 more Smart Citation
“…Similar to DIPNs contaminant, concentration of PMN in green mussel was relatively higher than that in fish, crab, and shrimp. Even though m-terphenyl was not detected in seafood from Jakarta Bay, this compound is present in water and sediment samples as reported by Dwiyitno et al (2015) that indicates contamination occurrence at lower concentration and/or less persistence than DIPNs and PMN. This could be seen from the lower octanol/water coefficient (log K ow ) of mterphenyl (5.52) compared to that of DIPNs (6.08).…”
Section: Contamination Of Dipns In Seafood Samples Frommentioning
confidence: 52%
“…Those contaminants are delivered from various sources, such as domestic disposal, industrial waste, transportation, oil spills, etc. (Takarina & Adiwibowo, 2010;Arifin, Puspitasari, & Miyazaki, 2012;Dwiyitno et al, 2015Dwiyitno et al, & 2016Dzikowitsky et al, 2016). Terrestrial pollution load has been shown in Jakarta Bay, as 39% of river water from Jakarta City was categorized as highly polluted and 44% was moderately polluted (BPLHD Jakarta, 2018).…”
Section: List Of Abbreviationsmentioning
confidence: 99%
“…Fewer comprehensive screening studies have addressed the lower trophic levels of ecosystems. In 2015, Dwiyitno et al [ 71 ] identified over 60 individual organic compounds including DDTs, high molecular weight polycyclic aromatic hydrocarbons (HMW-PAHs), and several emerging contaminants in six species of demersal and 2 pelagic fishes, banana shrimp ( Penaeus merguiensis ), and green mussel ( Perna viridis ) species from Jakarta Bay. According to the authors, some of these emerging contaminants had never previously been reported in Asian waters, namely diisopropylnaphthalenes (DIPNs), dichlorobenzene, DDMU, and phenylmethoxynaphthalene.…”
Section: Resultsmentioning
confidence: 99%
“…To widen the scope of future studies, derivatization may be considered. However, most derivatives are unstable [ 30 , 71 ] and interfering compounds may be introduced or formed upon derivatization, which may hamper data processing and identification. It may therefore be preferable to determine AHSs of these types using HPLC-HRMS [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A sampling campaign was performed at 20 stations in Jakarta Bay to cover an area of about 514 km 2 from Tanjung Pasir in the west to Tanjung Karawang in the east (5.8ºS-6.2ºS and 106.6ºE-107.1ºE) as presented in Figure 1. Sampling points were stratified purposively based on terrestrial inputs into three zones (western, middle, and eastern) part of Jakarta Bay (Cordova & Nurhati, 2019) and sea depth (Dwiyitno et al, 2015). These three zones were classified based on different terrestrial emission characteristics due to different land uses and population density.…”
Section: Study Locationmentioning
confidence: 99%